Sistemática de los saurios Anadia Gray, 1845 (Squamata: Gymnophthalmidae) de Ecuador: límite de especies, distribución geográfica y descripción de una especie nueva. Issue 1 (30th November 2018) - Betancourt, Raquel; Reyes-Puig, Carolina; Lobos, Simón E.; Yánez-Muñoz, Mario H.; Torres-Carvajal, Omar
ABSTRACT: We performed a systematic review of the genus Anadia in Ecuador to delimit species based on several lines of evidence: external morphology, hemipenes, coloration, DNA sequences and geographical distribution. We describe a new species, Anadia buenaventura sp. nov., which is distinguished from other species of Anadia by presenting a pattern of coloration with light dorsolateral bands and paravertebral rows of dark spots, as well as fewer scales around the body. We also present new data on the distribution of Anadia petersi Oftedal and a molecular phylogeny that suggests that Anadia rhombifera (Günther) is a complex of species that requires further taxonomic work that should include material from Colombia.